2009
DOI: 10.1089/neu.2008.0663
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward the Elderly with CNS Trauma: A Cross-Sectional Study of Neuroscientists, Clinicians, and Allied-Health Professionals

Abstract: Despite the potential impact of ageist attitudes on outcomes of central nervous system (CNS)-injured patients, little has been reported on this issue. Given this, we sought to conduct a questionnaire-based survey to assess the attitudes toward the elderly among basic and clinical neuroscientists, clinicians, and allied-health professionals whose research or medical practice is focused on neurotrauma. We also reviewed all abstracts presented in the National Neurotrauma Symposia from 1984 to 2007 and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Some recent Canadian research indicated that different health care practice settings and whether a student or practitioner is male or female may also be factors in attitudes towards elderly persons (Furlan & Fehlings, 2009). This is of interest given that occupational therapy, a traditionally gendered profession, is seeing small but steady growth towards a more balanced representation of both men and women enrolled in training programs and, subsequently, in the profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some recent Canadian research indicated that different health care practice settings and whether a student or practitioner is male or female may also be factors in attitudes towards elderly persons (Furlan & Fehlings, 2009). This is of interest given that occupational therapy, a traditionally gendered profession, is seeing small but steady growth towards a more balanced representation of both men and women enrolled in training programs and, subsequently, in the profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been suggested that among health professionals, occupational therapists and their students hold more positive attitudes toward older adults compared with their colleagues and are not as influenced by societal negative attitudes with regard to clinical decision making (e.g., Giles, Paterson, Butler, & Stewart, 2002;Horowitz, Savino, & Krauss, 1999;Weir, 2004). However, recent publications suggest that ageism continues to exist (e.g., Furlan & Fehlings, 2009;Kane, Lacey, & Green, 2009;Phelan, 2008). Indeed, despite awareness of the need for increased capacity in geriatric medicine, medical students' negative stereotypic attitudes toward older people did not improve between 1986 and 1994 (Wilkinson & Ferraro, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…9 Ageism has been reported in different areas of medicine including Oncology, Critical Care Medicine and Cardiology, as well as in clinical research. 10 In our study, nurses working in the rehabilitation setting hold similar attitudes towards older people to individuals with SCI, whereas nurses working in the rehabilitation setting showed fewer negative attitudes towards older individuals than nurses working in the acute-SCI-care setting. The nurses' attitudes towards older people were also analyzed in two earlier studies that compared different settings.…”
Section: Discussionmentioning
confidence: 44%
“…Numerous investigations have suggested that women hold more positive attitudes towards older individuals than men. 10,13,16,18 However, two earlier studies reported that male and female health-care professionals or students did not significantly differ regarding their attitudes towards older people. 19,20 Our analysis did not include gender as a potential factor associated with the attitudes towards older people because all nurses who responded to the survey were women.…”
Section: Discussionmentioning
confidence: 95%